Reliance Jamnagar - Reliance Industries Limited (2023)
In 1999, Shri Dhirubhai Ambani commissioned Reliance Jamnagar, the world’s largest greenfield grassroots refinery. Shri Mukesh Ambani led the team, and the refinery was operational in just 36 months. Reliance Jamnagar was a fully integrated unit, with a power-generation complex, a terminal complex, a port, and an entire township.